2018
DOI: 10.1186/s13223-018-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

A bronchoprotective role for Rgs2 in a murine model of lipopolysaccharide-induced airways inflammation

Abstract: BackgroundAsthma exacerbations are associated with the recruitment of neutrophils to the lungs. These cells release proteases and mediators, many of which act at G protein-coupled receptors (GPCRs) that couple via Gq to promote bronchoconstriction and inflammation. Common asthma therapeutics up-regulate expression of the regulator of G protein signalling (RGS), RGS2. As RGS2 reduces signaling from Gq-coupled GPCRs, we have defined role(s) for this GTPase-activating protein in an acute neutrophilic model of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
(106 reference statements)
0
25
0
Order By: Relevance
“…Pulmonary dysfunction begins following lung infection in sepsis-induced ALI mainly due to the release of proinflammatory mediators, such as TNF-α, IL-1β, and IL-6, leading to the loss of alveolar-capillary barrier integrity, neutrophil recruitment, and alveolar edema (Prescott & Angus, 2018). In a previous study, George et al reported that baseline resistance and compliance were not different between LPS-and PBS-exposed mice at 3 h, 6 h, and 24 h after LPS exposure (George, Chakraborty, Giembycz, & Newton, 2018). However, 3 h after LPS exposure, Mch (10-300 mg/ml) challenge induced significantly higher increases in lung resistance than PBS exposure alone.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary dysfunction begins following lung infection in sepsis-induced ALI mainly due to the release of proinflammatory mediators, such as TNF-α, IL-1β, and IL-6, leading to the loss of alveolar-capillary barrier integrity, neutrophil recruitment, and alveolar edema (Prescott & Angus, 2018). In a previous study, George et al reported that baseline resistance and compliance were not different between LPS-and PBS-exposed mice at 3 h, 6 h, and 24 h after LPS exposure (George, Chakraborty, Giembycz, & Newton, 2018). However, 3 h after LPS exposure, Mch (10-300 mg/ml) challenge induced significantly higher increases in lung resistance than PBS exposure alone.…”
Section: Discussionmentioning
confidence: 99%
“…These include the regulator of G-protein signalling, RGS2, which attenuates signal transduction from G-protein coupled receptors (GPCRs) that act via Gq (Heximer, 2004;Kimple et al, 2011). In vivo, including in models of lung inflammation (George et al, 2017;George et al, 2018;Jiang et al, 2015;Xie et al, 2012), RGS2 is bronchoprotective (Holden et al, 2011). Moreover, in HBECs and smooth muscle cells, LABAs synergize with glucocorticoids to enhance and prolong RGS2 expression (Holden et al, 2011;Holden et al, 2014).…”
Section: Downloaded Frommentioning
confidence: 99%
“…They also highly express Gnai2 , with a lower amount of Gnai3 (approximately 1/5 the amount as assessed by RNA sequencing) and little or no Gnai1 or Gnao . Loss of Rgs2 in mice increases neutrophil recruitment to inflamed lungs ( 12 , 13 ). Despite its low expression level, loss of Rgs5 in mice also leads to a more robust recruitment of neutrophils to inflamed lungs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%